Sistem Pendidikan Nahwu-Sharaf di Pondok Pesantren Al Bidayah dan Daya Tarik Masyarakat Malaysia untuk Belajar di Pesantren Al Bidayah - Muhammad Tis Asuh Sobirin; Titin Nurhidayati; Abdus Salam (AL-Ikhtiar : Jurnal Studi Islam, 2026)
This study aims to analyze the Nahwu-Sharaf education system at Al-Bidayah Islamic Boarding School and to identify the factors that make this educational system attractive to Malaysian students pursuing Islamic education in Indonesia. This research employed a qualitative approach using a case study design. The study was conducted at Al-Bidayah Islamic Boarding School, Jember, involving the head of the boarding school, teachers, and Malaysian students as research informants. Data were collected through observation, in-depth interviews, and documentation, and were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings reveal that the Nahwu-Sharaf education system is developed through a systematic curriculum, the implementation of the Al-Bidayah Method, peer teaching, memorization practices, continuous learning motivation, and the visionary leadership of the kyai. These educational components have successfully enhanced students’ competence in reading and understanding classical Islamic texts (kitab kuning), thereby strengthening the trust of the Malaysian community. The interest of Malaysian students is influenced by the boarding school's academic reputation, recommendations from Islamic teachers in Malaysia, the dissemination of learning through digital media, parental support, and the success of alumni in implementing the Al-Bidayah Method in Malaysia. This study concludes that the integration of leadership, educational system, academic culture, and instructional innovation constitutes the primary factor contributing to the attractiveness of Al-Bidayah Islamic Boarding School as a destination for Islamic education among the Malaysian community. Abstrak Penelitian ini bertujuan untuk menganalisis sistem pendidikan Nahwu-Sharaf di Pondok Pesantren Al-Bidayah serta mengungkap faktor-faktor yang menjadikan sistem tersebut sebagai daya tarik masyarakat Malaysia untuk menempuh pendidikan di Indonesia. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Penelitian dilaksanakan di Pondok Pesantren Al-Bidayah Jember dengan melibatkan pengasuh pesantren, ustaz, dan santri asal Malaysia sebagai informan. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi, kemudian dianalisis menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, serta penarikan kesimpulan. Keabsahan data diperoleh melalui triangulasi sumber dan triangulasi teknik. Hasil penelitian menunjukkan bahwa sistem pendidikan Nahwu-Sharaf di Pondok Pesantren Al-Bidayah dibangun melalui kurikulum yang sistematis, penerapan Metode Al-Bidayah, strategi peer teaching, pembiasaan hafalan, penguatan motivasi belajar, serta kepemimpinan kiai yang visioner. Sistem pendidikan tersebut berhasil membentuk kompetensi santri dalam membaca dan memahami kitab kuning, sehingga memperoleh kepercayaan masyarakat Malaysia. Ketertarikan masyarakat Malaysia dipengaruhi oleh reputasi akademik pesantren, rekomendasi guru di Malaysia, publikasi pembelajaran melalui media digital, dukungan orang tua, serta keberhasilan alumni dalam mengembangkan Metode Al-Bidayah di negara asalnya. Penelitian ini menyimpulkan bahwa integrasi antara kepemimpinan, sistem pembelajaran, budaya akademik, dan inovasi metode menjadi faktor utama yang memperkuat daya tarik Pondok Pesantren Al-Bidayah sebagai tujuan pendidikan Islam bagi masyarakat Malaysia.